The Existence of an Emergency Situation with Compelling Urgency Based on The Formula of The Article of The 1945 Constitution of The Republic Of Indonesia - Dewi, Lia Riesta; Suriyanti, Lili (Faculty of Law, Universitas Pekalongan, 2024)
The meaning of a state of emergency with a compelling urgency is very dependent on the meaning of the President's interpretation, because the President has the authority to determine when something is considered a state of emergency and when something is considered a state of urgency which causes this situation to create no legal certainty in determining a state of emergency or urgency coercive because everything really depends on the interpretation of the authority taken by a President based on his own legal interpretation because the 1945 Constitution of the Republic of Indonesia gives this authority to the President, while the 1945 Constitution of the Republic of Indonesia does not provide clear boundaries as to what is the definition of a state of emergency with a coercive urgency. This Research used Qualitative research methods. Qualitative research methods using normative juridical and empirical juridical approaches using primary data and secondary data. The result shows that State of emergency includes war emergency, military emergency and civil emergency which are based on situations that have actually occurred or are objective while for compelling emergencies based on the subjective circumstances of the president, with the standards set out in the Constitutional Court Decision Number 138/PUU-VII/2009. Determination of a state of danger which is the implementation of Article 12 of the 1945 Constitution of the Republic of Indonesia from 1946-2018 is contained in 12 laws and the urgency that compels the implementation of Article 22 of the 1945 Constitution of the Republic of Indonesia from 1960-2020 is contained in 134 Perppu issued by the President.